IGF2BP2 stabilized FBXL19-AS1 regulates the blood-tumour barrier permeability by negatively regulating ZNF765 by STAU1-mediated mRNA decay. Issue 12 (1st December 2020) - Liu, Xiaobai; Wu, Peiqi; Su, Rui; Xue, Yixue; Yang, Chunqing; Wang, Di; Ruan, Xuelei; Zheng, Jian; Yang, Yang; Li, Zhen; Liu, Yunhui
ABSTRACT: Blood-tumour barrier (BTB) has been known to significantly attenuate the efficacy of chemotherapy for glioma. In this report, we identified that insulin-like grown factor 2 mRNA-binding protein 2 (IGF2BP2) was over-expressed in glioma microvessel and glioma endothelial cells (GECs). Knockdown of IGF2BP2 decreased the expression of lncRNA FBXL19-AS1 and tight junction-related proteins, thereby promoting BTB permeability. FBXL19-AS1 was over-expressed and more enriched in the cytoplasm of GECs. In addition, FBXL19-AS1 could bind to 3ʹ-UTR of ZNF765 mRNA and down-regulate ZNF765 mRNA expression through STAU1-mediated mRNA decay (SMD). The low expression of ZNF765 was discovered in GECs and verified to increase BTB permeability by inhibiting the promoter activities of tight junction-related proteins. Meanwhile, ZNF765 also inhibited the transcriptional activity of IGF2BP2, thereby forming a feedback loop in regulating the BTB permeability. Single or combined application of silenced IGF2BP2 and FBXL19-AS1 improved the delivery and antitumor efficiency of doxorubicin (DOX). In general, our study revealed the regulation mechanism of IGF2BP2/FBXL19-AS1/ZNF765 axis on BTB permeability, which may provide valuable insight into treatment strategy for glioma.